Distribution characteristics of soil organic carbon and nitrogen in farmland and adjacent natural grassland in Tibet - Heman, Liu; Lihua, Cao; Changchang, Xu; Hong, Yang; Baoguo, Li (International Journal of Agricultural and Biological Engineering, 2016)
Land-use significantly affects soil organic carbon (SOC) and nitrogen cycling, eventually leading to global climate change. The cold and arid climate conditions in Tibet are not conducive to transformation of SOC and nitrogen. Hence, research on SOC and nitrogen distribution under different land-use patterns in Tibet is an important basis to assess the soil carbon and nitrogen potential in the land ecosystem of this area. This study aims to explain the effects of two land-use patterns, namely, farmland and grassland, on SOC and nitrogen contents in the cold regions of Tibet. This study also seeks to provide a scientific basis for the agricultural and grass production system. To achieve these goals, the changing features of total nitrogen (TN), mineralized nitrogen (nitrate nitrogen (NN) and ammonium nitrogen (AN)), and SOC were analyzed in different soil depths (0-5, 5-10, 10-20, 20-30, 30-40, and 40-50 cm) in farmland and adjacent natural grassland. The differences in carbon and nitrogen contents between the farmland and grassland of the main agricultural area of Tibet were determined through combined field survey and lab analysis. Results showed that the contents of SOC, TN and mineralized nitrogen in the grassland and farmland decreased with increasing soil depth mainly in the surface with depth of 0-20 cm. The effects of the different land-use patterns on the contents of SOC and TN were primarily evident in the 0-10 cm surface layer. The contents of SOC and TN in the farmland were significantly lower than those in the grassland, with mean reduction by 28.36% for SOC and 20.76% for TN. When the soil layer is deeper than 10 cm, the contents of SOC and TN in the farmland were greater than those in the grassland. This finding indicated that the transformation from grassland to farmland in Tibet mainly influenced the SOC and TN in the 0-10 cm surface layer. Moreover, the results showed that the increment of carbon in the deep soil layers of the farmland partially offsets the SOC loss from the surface because of cultivation. The ratio of mineralized nitrogen to TN in the farmland was significantly higher than that in the grassland (p<0.001). Mineralized nitrogen in the farmland mainly existed in the form of NN, with a mean content of 2.7% in the 0-50 cm surface layer. By contrast, the difference in the ratio of AN to TN between the grassland and farmland was not significant. The results revealed that the land-use pattern in extremely cold agricultural areas mainly affects the contents of SOC and nitrogen in the 0-10 cm surface layer, and agricultural management is beneficial in increasing the SOC content in the deeper layers. Keywords: Tibet, farmland, grassland, soil organic carbon, soil total nitrogen, nitrate nitrogen, ammonium nitrogen DOI: 10.3965/j.ijabe.20160901.2220 Citation: Liu H M, Cao L H, Xu C C, Yang H, Li B G. Distribution characteristics of soil organic carbon and nitrogen in farmland and adjacent natural grassland in Tibet. Int J Agric & Biol Eng, 2016; 9(1): 135－145.